Dynamic Security : the Democratic Therapeutic Community in Prison. - Parker, Michael, 1953- (Jessica Kingsley Publishers, 2006)
Dynamic Security describes the theory, practice and management of democratic therapeutic communities (TCs) in prisons using clinical examples and case studies. The contributors explore the complexities of working in TCs and the powerful emotional impact generated in the process of therapy in the forensic setting. In particular, they focus on the previous life history of offenders in therapy and on the effect of former relationship experiences on offenders' behaviour. This book is an indispensable reference for anyone working in the forensic field in prisons, secure hospitals or dangerous and s.